ANÁLISE TERMOGRAVIMÉTRICA E DIFRAÇÃO DE RAIO X DO COMPÓSITO METÁLICO, USANDO LIGNINAS - Cardoso, Aline; Cirilo, Armando; Rossi, Jesualdo Luiz; De Fátima, Adriana; Fernandes, Hedielle (ANAIS DO ENIC, 2018)
-